Self-Esteem and Job Performance: The Moderating Role of Self-Esteem Contingencies - FERRIS, D. Lance (Institutional Knowledge at Singapore Management University, 2009)
Although theoretical perspectives suggest self-esteem level (i.e., high/low) should have main and moderating effects on job performance, empirical and narrative reviews of the literature suggest such effects are either nonexistent or highly variable. To account for these mixed findings, we hypothesized that self-esteem level should only have main and moderating effects on job performance when one's self-esteem is not contingent upon workplace performance. Using multisource ratings across 2 samples of working adults, we found that the importance of performance to self-esteem (IPSE) moderated the effect of self-esteem level on job performance and moderated the buffering interaction between self-esteem level and role conflict in the prediction of job performance. Our results thus support IPSE as an important moderator of both main and moderating effects of self-esteem level.